Afrikaleidoskop meets ARTE | Screening and Discussion: Looted art in Benin City (Afrikaleidoskop meets ARTE, 2023)
The film program "AfriKaleidoscope" enters a new round. In cooperation with @ARTEde, the European culture channel the Cluster of Excellence "Africa Multiple" presents a series of films that focus on various important topics of the African continent. The first film is "Looted Art in Benin City," from the current series "Africa's New Museums" produced by ARTE. It was shown in May 2023, at @kunst-undkulturhausneunein8931 in Bayreuth. The film by Jean-Alexander "Sacha" Ntivyihabwa is dedicated to the equally famous and controversial Benin Bronzes, the most important art treasure of the Edo, which were looted by the British army from the palace of the ruler of the Kingdom of Benin in today's Nigeria in the late 19th century and sold off to museums in the global North, including Hamburg. After the film presentation, the filmmaker engaged in a discussion with the audience and scholars from the University of Bayreuth on the topic of restitution of art objects. Jean-Alexander "Sacha" Ntivyihabwa, born in 1964, is a studied Africanist, historian and passionate music and culture freak. Sacha Ntivyihabwa lives out his enthusiasm for TV making as managing partner of Signed Media, which is represented with its programs in the most important TV markets worldwide. In addition, Ntivyihabwa is also the founder of the anti-racist media watch association the "Brown Mob" and serves as an advisor to the association "Schotstek - scholarships for people with a migration background. He incorporates his intercultural experience and expertise into his TV programs and shares it as a speaker and lecturer at foundations and universities. The discussion was moderated by Prof. Dr. Ute Fendler, Chair of Romance Literary Studies and Comparative Literature with a special focus on Africa, and Dr. Cassandra Mark-Thiessen, historian and Junior Research Group Leader in the Cluster of Excellence.